Secuencia óptima de profundización de tajos a cielo abierto en yacimientos tabulares inclinados - Ortiz, Oswaldo (2014)
Optimum direction of advance of tabular inclined ore bodies can be established as the minimum stripping index and maximum ore recovery route. For either uniform o variable ore body grades, we can always establish at any depth a point for ore extraction which renders the highest income if an optimum deepening direction can be followed. This point can be located if ore body geologic and geometric parameters are known and applying basic mathematical principles. These final limits are fixed on vertical geological sections and do not require ore body block modeling. Accepting that any mineral deposit can be transformed approximately into an equivalent geometrical regular figure, the analysis can be applied to all mineral ore bodies thus, allowing rapid fixing of final excavation limits on surface.